The PATIENTS' VIEWS ON PHARMACY SERVICES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Understanding the full scope of patient satisfaction and its underlying factors is essential to enhancing service quality. Thus, the purpose of this study was to determine how satisfied patients were with pharmacy service. A cross-sectional research of 422 patients was carried out between September and January 2018 to evaluate patient satisfaction with pharmacy services at public hospitals in Eastern Ethiopian. Exit interviews using standardised questionnaires were used to gather data. Multiple logistic regression was used to examine the relationships between the dependent and independent variables using an adjusted odds ratio at a 95 percent confidence interval and the p values less than 0.05 to examine the associations.